A formação do gestor escolar e o conceito de inclusão no Programa Educação inclusiva: Direito a diversidade - Freitas, Flaviane Pelloso Molina; Schneckenberg, Marisa; de Oliveira, Jaima Pinheiro [UNESP]; Freitas, Carlos Cesar Garcia (My University, 2016)
This study aimed to analyze the official documents of the Inclusive Education: Right to Diversity in its decade of operation (2003-2103) to identify the formation of the proposed school manager and recognize the concept of school inclusion. It used bibliographic and documentary research and as a means to Content Analysis. It is evident that to meet the diversity and specificity of the student giving you the right to access to schools and quality education is essential that the school and school education be transformed.
Formation of school management and the concept of inclusion in INCLUSIVE Education program: Right to diversity
Keywords: Management; School inclusion; Training